Gender exposition in the select interview and speech of Miriam Defensor Santiago - Lawas, Lyra Erika; Magdadaro, Jehan; Pilapil, Jiza Mae; Minoza, Joemar (Universitas Negeri Semarang, 2025)
This research intends to expose the gender of Miriam Defensor Santiago using Women's Language Features by Robin Lakoff and Tannen's Difference Theory and the types of informal communication to determine Miriam Santiago's utterances in one interview on six topics and her speech at the University of Perpetual Help System as the main sources of data. Findings revealed that the selected interview and speech of Miriam Santiago have gender exposition. Analysis of the feminine or masculine language features of Miriam Santiago demonstrated that Robin Lakoff and Deborah Tannen's theories are significant in determining the language of one's sex. The study concludes that the language of Miriam Defensor Santiago is masculine. It recommends that the two theories from the 1970s and 1990s are still valuable for researching language and gender. Delving the language of Miriam Defensor Santiago in her younger years is recommended for future research.